Exploring the in vitro and in vivo compatibility of PLA, PLA/GNP and PLA/CNT‐COOH biodegradable nanocomposites: Prospects for tendon and ligament applications. Issue 8 (4th May 2017) - Correia Pinto, Viviana; Costa‐Almeida, Raquel; Rodrigues, Ilda; Guardão, Luísa; Soares, Raquel; Miranda Guedes, Rui
Abstract: Anterior cruciate ligament (ACL) reconstructive surgeries are the most frequent orthopedic procedures in the knee. Currently, existing strategies fail in completely restoring tissue functionality and have a high failure rate associated, presenting a compelling argument towards the development of novel materials envisioning ACL reinforcement. Tendons and ligaments, in general, have a strong demand in terms of biomechanical features of developed constructs. We have previously developed polylactic acid (PLA)‐based biodegradable films reinforced either with graphene nanoplatelets (PLA/GNP) or with carboxyl‐functionalized carbon nanotubes (PLA/CNT‐COOH). In the present study, we comparatively assessed the biological performance of PLA, PLA/GNP, and PLA/CNT‐COOH by seeding human dermal fibroblasts (HFF‐1) and studying cell viability and proliferation. In vivo tests were also performed by subcutaneous implantation in 6‐week‐old C57Bl/6 mice. Results showed that all formulations studied herein did not elicit cytotoxic responses in seeded HFF‐1, supporting cell proliferation up to 3 days in culture. Moreover, animal studies indicated no physiological signs of severe inflammatory response after 1 and 2 weeks after implantation. Taken together, our results present a preliminary assessment on the compatibility of PLA reinforced with GNP and CNT‐COOH nanofillers, highlighting the potential use of these carbon‐based nanofillers for the fabrication of reinforced synthetic polymer‐based structures for ACL reinforcement. © 2017 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 105A: 2182–2190, 2017.